A polymer-free, biomimicry drug self-delivery system fabricated via a synergistic combination of bottom-up and top-down approaches. Issue 47 (12th November 2018) - Xu, Xiaobao; Yang, Gaomai; Xue, Xiangdong; Lu, Hongwei; Wu, Hao; Huang, Yee; Jing, Di; Xiao, Wenwu; Tian, Jingkui; Yao, Wei; Pan, Chong-xian; Lin, Tzu-yin; et al.
Abstract : A pure drug self-delivery system with a cell membrane modified to create a unique class of ideal drug delivery platforms. Abstract : Compared to conventional carrier-assistant drug delivery systems (DDSs), drug self-delivery systems (DSDSs) have advantages of unprecedented drug loading capacity, minimized carrier-related toxicity and ease of preparation. However, the colloidal stability and blood circulation time of DSDSs still need to be improved. Here we report on the development of a novel biomimicry drug self-delivery system by the integration of a top-down cell membrane complexing technique into our self-delivery multifunctional nano-platform made from the bottom-up approach that contains 100% active pharmaceutical ingredients (API) pheophorbide A and irinotecan conjugates (named PI). Compared to conventional cell membrane-coated nanoparticles with a polymer framework as the core and a relatively low drug loading capacity, this system consisting of red blood cell membrane vesicle complexed PI (RBC-PI) is polymer-free with up to 50% API loading. RBC-PI exhibited 10 times higher area under curve in a pharmacokinetic study and a much lower macrophage uptake compared with the parent PI nanoparticles. RBC-PI retained the excellent chemophototherapeutic effects of the PI nanoparticles, but possessed superior anti-cancer efficacy with prolonged blood circulation, improved tumor delivery, and enhanced photothermal effects in animal models. This system represents a novel example of using a cell membrane complexing technique for the effective surface modification of DSDSs. This is also an innovative study to form a polymer-free cell membrane nanoparticle complexing with positive surface-charged materials. This biomimicry DSDS takes advantage of the best features from both systems to make up for each other's shortcomings and provides all the critical features for an ideal drug delivery system.